The effects of additives on the reduction of the pour point of diesel fuel and fuel oil. (16th September 2016) - Farazmand, S.; Ehsani, M. R.; Shadman, M. M.; Ahmadi, S.; Veisi, S.; Abdi, E.
ABSTRACT: One important industrial problem is the wax precipitation of oil fractions. Factors such as oil composition, temperature, and pressure are effective in causing wax precipitation. One way to prevent wax precipitation is using of chemical inhibitors to reduce pour point. Studying the effects of additives on specific oil samples could help solve wax precipitation problems at various oil processing stages. Despite previous studies that have been done at this aim, finding materials that could decrease the pour point and be economically acceptable, environmentally well optimized, and reasonable is still an unsolved problem. So, it is important to make use of effective materials that could be influential in preventing of wax precipitation or reduction of the amount of precipitation and thus decrease the pour point temperature. In this study, the effects of industrial polymer additives and surfactants that are economically acceptable on decrement of pour point temperature were studied by using three oil product samples, namely light diesel, heavy diesel, and fuel oil (Purification Company of Esfahan). Furthermore, optimized type and concentration of the additives were studied. Results showed that copolymer ethylene-vinyl acetate 28% at a concentration of 500 ppm reduced pour point temperature by 12°C for diesel and that copolymer ethylene-vinyl acetate 19% at a concentration of 300 ppm reduced pour point temperature by 9°C for fuel oil.